Preparation process of soft magnetic iron core bar for pump

Through the preparation process, the iron oxide, nickel, niobium, molybdenum and other elements are mixed and combined with the magnetic powder glue of lotus root extract, the problem of insufficient uniformity of the iron core magnetic rod is solved, and the opening and closing stability of the solenoid valve and the precise adjustment ability of the fluid flow are improved.

CN119864215AInactive Publication Date: 2025-04-22绍兴康健材料科技股份有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510354075.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the insufficient uniformity of the iron core magnetic rod, the valve opening and closing is not stable enough, which affects the precise adjustment of fluid flow.

Method used

Using a preparation process of a soft magnet core rod for pump, iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and dispersant are mixed in water, spray granulation, preheating treatment and reducing heat treatment, iron nickel niobium molybdenum soft magnetic powder is obtained, and mixed with magnetic powder glue containing lotus root extract to press into rod rod.

Benefits of technology

The uniformity of the iron core magnetic rod is improved, the flowability and magnetic properties of magnetic powder are enhanced, the uniformity of magnetic force line distribution is ensured, and the opening and closing stability of the solenoid valve and the precise adjustment ability of the fluid flow are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864215A_ABST
    Figure CN119864215A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a soft magnetic iron core bar for a pump, and the preparation process comprises the following steps: uniformly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersing agent in water to obtain slurry; carrying out spray granulation on the slurry to obtain a granulated material; carrying out preheating treatment on the granulation material in an inert atmosphere; carrying out reduction heat treatment on the preheated granulated material in a reducing gas atmosphere to obtain iron-nickel-niobium-molybdenum alloy powder; annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain iron-nickel-niobium-molybdenum soft magnetic powder; and mixing epoxy resin, a coupling agent and a lotus root extract to prepare magnetic powder glue, mixing the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing into bars. According to the scheme, the soft magnetic powder and the magnetic powder glue containing the lotus root extract are mixed and refined, and polysaccharide and polyphenol substances in the lotus root extract can improve the fluidity of the magnetic powder and reduce generation of pores, so that the powder is more uniformly mixed, and a subsequent forming process is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic rod production, in particular to a preparation process of a soft magnetic core rod for a pump. Background Art

[0002] The iron core magnetic rod is an important component in the solenoid valve for controlling the opening and closing of the valve. The magnetic rod controls the opening and closing of the valve through electromagnetic action, and is usually used in conjunction with the electromagnetic coil. When current passes through the electromagnetic coil, a magnetic field is generated, causing the magnetic rod to attract the iron valve core to open the valve; when the current is disconnected, the magnetic field disappears, the magnetic rod's attraction to the valve core weakens or disappears, and the valve closes. ‌ By adjusting the size and direction of the current, the degree of opening of the valve can be accurately controlled, thereby adjusting the flow and pressure of the fluid. ‌ At present, for solenoid valves with large flow rates, the opening and closing time and position of the valve core are important factors for precise flow control, which is closely related to the uniformity of the iron core magnetic rod. The high uniformity of the iron core magnetic rod means that its magnetic permeability is consistent in all parts. When the electromagnetic coil is energized to generate a magnetic field, the iron core magnetic rod can be magnetized evenly, and the hysteresis loss and eddy current loss are relatively small, forming a uniform distribution of magnetic lines of force. The electromagnetic force generated in this way is more uniform and stable, and can act on the valve core more accurately to push it to move. The force points of the valve core are evenly distributed, and the valve core will not be offset due to excessive or insufficient local force, thereby ensuring that the valve core can move smoothly along the predetermined trajectory, ensuring the precise control of the valve core opening, and thus achieving precise regulation of the fluid flow. When the valve core moves smoothly along the predetermined trajectory, the cross-sectional area of ​​the fluid channel changes evenly, and the resistance and disturbance to the fluid flow are small, so that the fluid flow is more stable and there will be no sudden changes. However, the existing solenoid valve releases different fluid flow rates each time (such as coffee machines), and the opening and closing of the valve is not stable enough. Summary of the invention

[0003] The main purpose of the present invention is to propose a preparation process of a soft magnetic core rod for a pump, aiming to solve the current technical problem of unstable opening and closing of the solenoid valve caused by insufficient uniformity of the core magnetic rod.

[0004] To achieve the above object, the present invention provides a preparation process of a soft magnetic core rod for a pump, characterized in that the preparation process comprises the following steps: Evenly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry; The slurry is subjected to spray granulation to obtain granulated material; The granulated material is preheated in an inert atmosphere; The preheated granulated material is subjected to reduction heat treatment in a reducing gas atmosphere to obtain an iron-nickel-niobium-molybdenum alloy powder; annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain iron-nickel-niobium-molybdenum soft magnetic powder; The epoxy resin, the curing agent, the coupling agent and the lotus root extract are mixed to prepare the magnetic powder adhesive, and the iron-nickel-niobium-molybdenum soft magnetic powder is mixed with the magnetic powder adhesive and pressed into rods.

[0005] Optionally, in the step of uniformly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry, the dispersant is selected from one or two of polyvinyl alcohol and polyacrylic acid.

[0006] Optionally, in the step of uniformly mixing the iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and the dispersant in water to obtain a slurry, the amount of the dispersant added to the slurry is 0.1-1 wt %.

[0007] Optionally, in the step of uniformly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry, a particle size D90 of the slurry is less than 2-5 μm.

[0008] Optionally, in the step of preheating the granulated material in an inert atmosphere, the preheating is performed according to the following temperature curve: 25~100℃ heating time 20~60min, 100℃ keeping time 20~100min; 100~300℃ heating time 20~100min, 300℃ keeping time 20~100min; Heating time at 300-1200℃ is 200-600min, keeping time at 1200℃ is 20-120min, cooling at 1200℃.

[0009] Optionally, in the step of subjecting the preheat-treated granulated material to reduction heat treatment in a reducing gas atmosphere to obtain the iron-nickel-niobium-molybdenum alloy powder, the temperature of the reduction heat treatment is 600-1200°C.

[0010] Optionally, in the step of annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain the iron-nickel-niobium-molybdenum soft magnetic powder, the annealing temperature is 400-800° C. and the annealing process is protected by reducing gas.

[0011] Optionally, in the step of mixing epoxy resin, curing agent, coupling agent and lotus root extract to prepare magnetic powder glue, kneading the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing them into rods, the mass ratio of epoxy resin, curing agent, coupling agent and lotus root extract is 100:(15~25):(1~2):(1~2).

[0012] Optionally, the preparation process of the lotus root extract is: take the tubers of white lotus root and yellow lotus root, wash them with deionized water, dry them to obtain a solid, use carbon dioxide as a solvent to perform supercritical extraction on the solid, concentrate it and put it into an ethanol solution for ultrasonic extraction and then filter it, collect the filtrate, centrifuge it, collect the supernatant, concentrate it and calcine it at 120-140°C to obtain the lotus root extract.

[0013] Optionally, in the step of mixing epoxy resin, coupling agent and auxiliary agent to prepare magnetic powder glue, mixing the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing them into rods, the mass ratio of the iron-nickel-niobium-molybdenum soft magnetic powder to the magnetic powder glue is (90~98):2.

[0014] In the technical solution of the present invention, soft magnetic powder is made of minerals of four elements: iron, nickel, niobium and molybdenum, and is mixed and refined with magnetic powder glue containing lotus root extract before pressing. The polysaccharides and polyphenols in the lotus root extract can increase the fluidity of the magnetic powder, reduce the generation of pores, and make the powder more evenly mixed to achieve a higher uniformity, so as to carry out the subsequent molding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0016] Figure 1 A schematic flow chart of an embodiment of a process for preparing a soft magnetic core rod for a pump provided by the present invention.

[0017] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0018] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0019] It should be noted that, in the embodiments, those without specifying specific conditions are carried out according to normal conditions or conditions recommended by the manufacturer. Those without specifying the manufacturer of reagents or instruments used are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, and "A and / or B" is taken as an example, including schemes A, B, or A and B that meet the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of the technical schemes is contradictory or cannot be achieved, it should be considered that the combination of such technical schemes does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work, all belong to the scope of protection of the present invention.

[0020] At present, for large-flow solenoid valves, the opening and closing time and position of the valve core are important factors for accurately controlling the flow rate, which is closely related to the uniformity of the iron core magnetic rod. However, the flow rate of the existing solenoid valves released by the fluid each time is different (such as coffee machines, etc.), and the opening and closing of the valve is not stable enough.

[0021] In view of this, the present invention proposes a preparation process of a soft magnetic core rod for a pump, combining Figure 1 The schematic flow diagram of the present invention is provided, and the steps of the preparation process are as follows.

[0022] Step S10: Evenly mix iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry.

[0023] In this embodiment, the dispersant is selected from one or both of polyvinyl alcohol and polyacrylic acid, and the amount of the dispersant added to the slurry is 0.1-1 wt %, and the particle size D90 of the slurry is less than 2-5 μm.

[0024] Step S20, spray granulation on the slurry to obtain granulated material.

[0025] In this embodiment, the slurry is pumped into a spray tower for spray granulation.

[0026] Step S30, preheating the granulated material in an inert atmosphere.

[0027] In this embodiment, the granulated material after the preheat treatment is subjected to reduction heat treatment in a reducing gas atmosphere to obtain the iron-nickel-niobium-molybdenum alloy powder. The temperature of the reduction heat treatment is 600-1200°C.

[0028] Step S40, subjecting the preheated granulated material to reduction heat treatment in a reducing gas atmosphere to obtain an iron-nickel-niobium-molybdenum alloy powder.

[0029] In this embodiment, in the step of preheating the granulated material in an inert atmosphere, the preheating treatment is carried out according to the following temperature curve: 25-100°C heating time 20-60min, 100°C insulation time 20-100min; 100-300°C heating time 20-100min, 300°C insulation time 20-100min; 300-1200°C heating time 200-600min, 1200°C insulation time 20-120min, 1200°C cooling to room temperature.

[0030] Step S50, annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0031] In this embodiment, in the step of annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain the iron-nickel-niobium-molybdenum soft magnetic powder, the annealing temperature is 400-800° C. and the annealing process is protected by reducing gas such as hydrogen.

[0032] Step S60, mixing epoxy resin, curing agent, coupling agent and lotus root extract to prepare magnetic powder glue, mixing the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing them into rods.

[0033] In this embodiment, the preparation process of lotus root extract is as follows: 100 parts of white lotus root and 200 parts of yellow lotus root tubers are taken by mass, washed with deionized water, dried at 60°C to obtain a solid, and the solid is subjected to supercritical extraction using carbon dioxide as a solvent. After concentration, the solid is placed in an ice-water solution and ultrasonically extracted for 10-30 minutes, then filtered, and the filtrate is collected. After centrifugation at 10000r / min for 10 minutes, the supernatant is collected, concentrated, and calcined at 120-140°C to obtain a lotus root extract.

[0034] In specific implementation, the mass ratio of iron-nickel-niobium-molybdenum soft magnetic powder to magnetic powder glue is (90-98):2. This technology uses polysaccharides and polyphenols in lotus root extract to enhance the interface bonding between magnetic particles and curing agents, which can increase the fluidity of magnetic powder, ensure that magnetic particles are evenly dispersed in the matrix, and reduce bubbles and surface porosity. Finally, the rods are electroplated with nickel for surface treatment to prevent rust. In addition, the magnetic powder glue with lotus root extract has better biocompatibility and is suitable for valve structures in the food industry.

[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention. Example 1

[0036] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide (purity 99%, the same below) with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100℃ heating time 40min, 100℃ maintenance The powder was heated to 100 ℃ - 300 ℃ for 60 min, kept at 300 ℃ for 60 min, heated to 300 ℃ - 1200 ℃ for 400 min, kept at 1200 ℃ for 80 min, and cooled to room temperature with the furnace after being kept at 1100 ℃; the preheated powder was reduced with hydrogen, and treated at 1000 ℃ for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500 ℃ for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder, and the magnetic properties were tested.

[0037] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2.5:1, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 98:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0038] Table 1: Example 2

[0039] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0040] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2.3:1.2, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 98:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0041] Table 2: Example 3

[0042] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0043] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2:1.5, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 98:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0044] Table 3: Example 4

[0045] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0046] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2.5:1, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 90:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0047] Table 4: Example 5

[0048] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0049] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2.5:1, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 93:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0050] Table 5: Example 6

[0051] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0052] 100 parts of white lotus root and 200 parts of yellow lotus root tubers were taken by mass, washed with deionized water, dried at 60°C to obtain solids, and supercritically extracted with carbon dioxide as a solvent. After concentration, the solids were placed in an ice-water solution for ultrasonic extraction for 20 minutes and then filtered to collect the filtrate. After centrifugation at 10000r / min for 10 minutes, the supernatant was collected, concentrated and calcined at 130°C to obtain lotus root extract. Magnetic powder glue was prepared by mixing epoxy resin: curing agent (TaiLuck-D95 modified dicyandiamide): coupling agent (KH-560): lotus root extract in a weight ratio of 80:16.5:2.5:1, and iron-nickel-niobium-molybdenum soft magnetic powder and magnetic powder glue were mixed in a weight ratio of 95:2. After mixing, the powder fluidity and magnetic properties were tested, and the molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0053] Table 6: Comparative Example 1

[0054] Red iron oxide, nickel carbonate, niobium oxide and molybdenum oxide with a particle size D90 < 5 μm are weighed according to the composition ratio of Fe16Ni75Nb5Mo4 and added into a container, and then 0.5 wt% of polyvinyl alcohol accounting for the total mass of the slurry is added as a dispersant, and then water accounting for 60% of its volume is injected into the container, and stirred to obtain a slurry; the slurry is pumped into a spray tower for spray granulation to obtain a granulated material; the granulated material is preheated in a nitrogen environment, and the treatment temperature curve is 25-100°C heating time 40min, 100°C insulation 6 The powder was heated from 100°C to 300°C for 60 min, kept at 300°C for 60 min, heated from 300°C to 1200°C for 400 min, kept at 1200°C for 80 min, and cooled with the furnace after being kept at 1100°C to room temperature; the preheated powder was reduced with hydrogen, and treated at 1000°C for 6 h to obtain iron-nickel-niobium-molybdenum alloy powder; the iron-nickel-niobium-molybdenum alloy powder was reduced at 500°C for 3 h in a hydrogen atmosphere vacuum furnace, annealed to relieve stress, and the powder was sieved through a 200-mesh sieve to obtain iron-nickel-niobium-molybdenum soft magnetic powder.

[0055] The magnetic powder adhesive was prepared by mixing epoxy resin and curing agent (TaiLuck-D95 modified dicyandiamide) at a weight ratio of 85:15. The iron, nickel, niobium, and molybdenum soft magnetic powders were mixed with the magnetic powder adhesive at a weight ratio of 98:2. After mixing, the powder fluidity and magnetic properties were tested. The molding pressure was 10T / cm 2 The mixed powder is pressed into a magnetic rod Φ7.5mm×30mm according to the standard.

[0056] Table 7:

[0057] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A process for preparing a soft magnetic core rod for a pump, characterized in that: The preparation process comprises the following steps: Evenly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry; The slurry is subjected to spray granulation to obtain granulated material; The granulated material is preheated in an inert atmosphere; The preheated granulated material is subjected to reduction heat treatment in a reducing gas atmosphere to obtain an iron-nickel-niobium-molybdenum alloy powder; annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain iron-nickel-niobium-molybdenum soft magnetic powder; The epoxy resin, the curing agent, the coupling agent and the lotus root extract are mixed to prepare the magnetic powder adhesive, and the iron-nickel-niobium-molybdenum soft magnetic powder is mixed with the magnetic powder adhesive and pressed into rods.

2. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of uniformly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry, the dispersant is selected from one or two of polyvinyl alcohol and polyacrylic acid.

3. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of uniformly mixing the iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and the dispersant in water to obtain the slurry, the amount of the dispersant added to the slurry is 0.1-1 wt %.

4. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of uniformly mixing iron oxide, nickel carbonate, niobium oxide, molybdenum oxide and a dispersant in water to obtain a slurry, the particle size D90 of the slurry is less than 2-5 μm.

5. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of preheating the granulated material in an inert atmosphere, the preheating is performed according to the following temperature curve: 25~100℃ heating time 20~60min, 100℃ keeping time 20~100min; 100~300℃ heating time 20~100min, 300℃ keeping time 20~100min; Heating time at 300-1200℃ is 200-600min, keeping time at 1200℃ is 20-120min, cooling at 1200℃.

6. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of subjecting the preheated granulated material to reduction heat treatment in a reducing gas atmosphere to obtain an iron-nickel-niobium-molybdenum alloy powder, the temperature of the reduction heat treatment is 600-1200°C.

7. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of annealing, cooling and sieving the iron-nickel-niobium-molybdenum alloy powder to obtain the iron-nickel-niobium-molybdenum soft magnetic powder, the annealing temperature is 400-800° C. and the annealing process is protected by reducing gas.

8. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of mixing epoxy resin, curing agent, coupling agent and lotus root extract to prepare magnetic powder glue, kneading the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing them into rods, the mass ratio of epoxy resin, curing agent, coupling agent and lotus root extract is 80: (15-25): (2-2.5): (1-1.5).

9. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: The preparation process of the lotus root extract is as follows: taking tubers of white lotus root and yellow lotus root, washing them with deionized water, drying them to obtain solids, using carbon dioxide as a solvent to perform supercritical extraction on the solids, concentrating them, putting them into an ethanol solution for ultrasonic extraction, filtering them, collecting the filtrate, centrifuging them, collecting the supernatant, concentrating them, and calcining them at 120-140° C. to obtain the lotus root extract.

10. The process for preparing the soft magnetic core rod for pump according to claim 1, characterized in that: In the step of mixing epoxy resin, coupling agent and auxiliary agent to prepare magnetic powder glue, kneading the iron-nickel-niobium-molybdenum soft magnetic powder with the magnetic powder glue, and pressing them into rods, the mass ratio of the iron-nickel-niobium-molybdenum soft magnetic powder to the magnetic powder glue is (90-98):2.

Citation Information

Patent Citations

  • Universal type aquatic collagen peptide food for wound healing

    CN105982331A

  • Preparation method of iron-nickel-molybdenum soft magnetic powder

    CN111375782A

  • Preparation method and material of metal soft magnetic core applied to ultrahigh frequency

    CN113674979A

  • Production process of soft magnetic coupling permanent magnet bonded composite magnet

    CN114783759A

  • Low-loss high-entropy alloy soft magnetic powder core and preparation method thereof

    CN118737678A